PERANCANGAN POP UP BOOK AND SOUND TEMBANG DOLANAN SEBAGAI MEDIA PENGENALAN ALAT MUSIK GAMELAN - Asya Ari, Ilham Musyafa; Handriyotopo, Handriyotopo (ISI Press Institut Seni Indonesia Surakarta, 2020)
One traditional Javanese art is the art of tembang dolanan which is accompanied by Javanese gamelan. Currently in school subjects, elementary school students in Surakarta are very rarely introduced, because in fact the gamelan instruments are not owned or rarely exist as a learning laboratory. Learning dolanan songs accompanied by gamelan instruments are considered less interesting and outdated, although there is a campursari instrument or single organ. The design of this pop up book book of dolanan tembang was created, as a new teaching medium aimed to make it more interesting for today's generation, especially for elementary school children to get to know the culture of traditional music which is full of meaning whose existence has been forgotten. This method of creation begins with research and interviews to elementary schools in Surakarta, brainstorming, exploring ideas, creating manuscripts, sketches, layouts, dummy, and artwork. Promotional media to introduce Pop up book is through the media of the top line of the website or social media and supporting media such as color pencils, totegbag, pins and stickers, as a form to awaken the importance of loving the local culture in tembang dolanan.